Status and challenges of black soils - Fontana, Ademir; Labaz, Beata; Monger, Curtis; Morras, Hector; Wang, Lei; Pfeiffer, Marco; Taboada, Miguel Angel; Valle, Susana (FAO, 2022)
Although black soils account for only 8.2 percent of the Global Land Area (FAO, 2022a), they are of paramount importance for food security, as highlighted by the UN Sustainable Development Goal 2 (i.e to end hunger, achieve food security and improve nutrition, and promote sustainable agriculture by 2030). The general category of black soils includes three main soil groups Chernozem, Kastanozem and Phaeozem, according to the World Reference Base for Soil Resources (WRB). Black soils are characterized by their thick, dark-coloured, and humus-rich topsoil. In general terms, black soils have granular and subangular blocky structure, optimal bulk density, and high amounts of plant nutrients. However all these favorable properties are only present in soils within virgin or quasi-pristine ecosystems, which are now rare (Montanarella et al., 2021). There are other soil types also considered as black soils, as for example, swelling soils (Vertisols), volcanic soils (Andisols), anthropogenic soils, among others. Not all of them strictly comply with some of the conditions indicated for the Category 1 of black soil definition (such as having been formed under grassland vegetation) (FAO, 2019), but they all have some characteristics in their profiles that allow them to be classified as black soils, such as having a thick, darkcoloured, and humus-rich topsoil. Apart from being highly productive lands, blac k soils are responsible for multiple ecosystem services such as water retention, maintenance of soil biodiversity from microorganism to megafauna, and soil fertility, and prevention of soil compaction and waterlogging. One of the most valuable services is accumulation of great amounts of SOC in a relatively stable form. Black soils are one of the most important pools of carbon accounting for 8.27 percent (56 PgC) of the total global SOC stock in the top 30 centimetres of the soil (FAO, 2022d). These carbon stores are, however, endangered by the processes of organic carbon loss due to the accelerated humus oxidation under cultivation. In many places the loss of humus and nutrient mining are the most important threats to black soils because these soils are considered as highly fertile “by nature” and thus have not needed application of organic and mineral fertilizers. Black soils are under further threat from various physical, chemical, and biological degradation processes (FAO and ITPS, 2015). Some of these processes are easily reversible through sustainable soil management practices, such as nutrient imbalance, compaction, and structural degradation. However, other processes are difficult to reverse. First, soil loss due to erosion (wind, water and meltwater), is the most widespread threat in all world’s soils. Wind erosion is a problem that tremendously affected the Midwestern of the United States of America (the infamous Dust Bowl in the 1930s) and west Siberia and north Kazakhstan in the ex-Union of Soviet Socialist Republics (USSR) during the development of virgin lands in 1950s. Currently, soil salinization is becoming a growing problem, especially in irrigated areas in the most arid parts of the distribution of black soils. Second, land use change for food production exacerbates unsustainable management practices such as aggressive tillage and overgrazing furthering losses due to erosion. Diffuse pollution processes affect black soils devoted to fibre agriculture. This happens for various reasons, including the use of inappropriate fertilization technologies with high doses of nitrogen and phosphorus fertilizers and manures, or the excessive or inadequate use of herbicides and pesticides whose decomposition products are potential contaminants in soils, streams and groundwater. Finally, many black soils are threatened by soil sealing, due to the advance of urban areas and infrastructure in overpopulated regions or countries. This advance makes thousands of hectares of previously black soils destined for food production disappear.